Imagi(ni)ng post-independence Zimbabwe: political transition and the rhetoric of transformation in the liberation war literature. - Viriri, Advice (2016)
The article seeks to stimulate debate about Zimbabwe’s liberation struggle, with a special focus on engagements in and around the rhetoric on the transformation that the transition of the promises of independence would usher in. It further asserts that the principal aim of the struggle was the rhetoric of land redistribution in the post-independence era imbued in the current dialectic between transition and transformation. With this research, it is hoped that such stimulation on the rhetoric of transformation on the African continent as depicted through African literature’s subsequent contributions reveal a deeply contested terrain which fosters the development of a balanced account of the struggle for the benefit of posterity. This selected war literature mirrors a period of national reconstruction that is characterised by writers who register not only the joys and pains of national rebirth, but writers who begin to constitute a critical consciousness embedded within the context of developmental politics. This literature laments the failure to fulfill most of the aspirations after Zimbabwe’s independence. It examines the consequence of the regression of the liberation movement into nationalism that focused on the transfer of power from the Rhodesian regime to the African nationalists, rather than the transformation of society to realise the ideals of the liberation struggle. This left all the despotic Rhodesian institutions and statutes intact and this could hardly have facilitated the outcome of what the struggle stood for. It is intriguing that the common liberation war rhetoric deliberately eulogises the contribution of the war veterans who negate what the liberation movement stood for before and after independence. It is through this rhetoric of transition and transformation that Zimbabwe’s current socio-political dire straits are no more than the inevitable consequence and outcome of two decades of misguided economic policies founded on populism, politics of patronage, mismanagement, incompetence and corruption.